Önitatók konstrukciós és hidromechanikai vizsgálata - Dávidházy, Sándor (Acta Agraria Debreceniensis, 2002)
Our research aimed to examine Hungarian automatic drinking system constructions and hydromechanics under laboratory conditions and in operation with special emphasison the small volume, valve types. Considering that no Hungarian standard of automatic drinking system examination and qualification exists, on the basis of technical literature, the new examination method of automatic drinking systems has been elaborated. For laboratory measurements, a universal measuring bench was assembled which is applicable to the hydromechanic testing of all automatic drinking systems (cattle, sheep, pig). Summary of the laboratory measurements: Upon comparison of the flow capacity of the valves, in the case of same opening values (h/dn), the rubber spring valve of SZI type automatic fountain has the highest flow capacity, although in the case of 100 kPa pressure even this type has only 15-16 l/min value which hardly surpasses the lower limit of the desired 15-25 l/min range. The loss coefficients of the valves, on investigating in the range 100-200 kPa, showed the lowest value (2,2-5,8) with the steel spring self drinking device. Summary of the operational investigations: In the long term operational investigations, the rubber stripped valve and the rubber spring automatic fountains had the most favourable operational reliability values: K4=0,98 and K4=0,94, respectively. From the aspect of animal operation of the valves, all the Hungarian types are frontal operated, thus such system automatic valve drinking devices can be used only in long and moderately long stands, directed toward the animal. On the basis of hydromechanical and construction examinations of the Hungarian tied cattle production technology the construction modification of the rubber spring valve of SZI type automatic drinking fountain, which is the most frequantly used in this country, was carried out. Due to design modifications the valve parameters improved significantly. The goals of the accomplished valve modification were ζ’sz – loss coefficient to be reduced q – flow capacity to be increased